Mechanism of decomposition of aromatics over charcoal and necessary condition for maintaining its activity - Hosokai, S.; Kumabe, K.; Ohshita, M.; Norinaga, K.; Li, Chun-Zhu; Hayashi, J. (Elsevier Science Ltd, 2008)
Decomposition of mono- to tetra-aromatics over charcoal was investigated under conditions such as temperature; 700–900 °C, inlet concentrations of aromatics, steam and H2; 7.5–15 g/Nm3, 0–15.5 vol% and 0–15.5 vol%, respectively, gas residence time within charcoal bed; 0.2 s, particle size of charcoal; 1.3–2.4 mm. The charcoal, with an initial surface area of 740 m2/g, was active enough to decompose naphthalene completely even at 750 °C. Aromatics with more rings per molecule were decomposed more rapidly. The aromatics were decomposed over the charcoal by coking rather than direct steam reforming irrespective of temperature and steam/H2 concentrations. The coking, i.e., carbon deposition from the aromatics, caused loss of micropores and thereby activity of the charcoal, while steam gasification of the charcoal/coke formed or regenerated micropores. Relationship between the overall rate of carbon deposition by the coking and gas formation by the gasification within the charcoal bed showed that progress of the gasification at a rate equivalent with or greater than that of the carbon deposition was necessary for maintaining the activity of the charcoal.